More Than a Game : A Case Study of Digital Value Co-Creation and Fan Engagement in Professional Sports - Heikkilä, Max (My University, 2025)
With the rise of digital transformation, sports fandom has evolved from passive viewing into an experience defined by emotional commitment and community. In this accelerating shift, fans are no longer just an audience but active participants who create content, engage in dialogue, and co-create experiences with sports organizations on digital platforms. This changing role of the fan presents both an opportunity and a challenge for sports organizations striving to maintain their relevance and financial viability in the competition for people's leisure time. The aim of this study is to investigate how a sports organization utilizes digital platforms and social media through this transformation, with the goal of deepening fan relationships and co-creating value with fans. The use of social media in sports marketing has often been studied from the perspective of organizational and communication strategies, leaving the practical processes of co-creation with less attention. To complement the existing research, this thesis delves into the mechanisms of value co-creation in a digital environment. The study examines this phenomenon from the perspective of a Finnish professional sports organization, where a passionate fan culture plays a significant role. The findings are based on a mixed-methods dataset collected through triangulation, consisting of interviews with the club's marketing representatives, a fan survey (n=671), and a content analysis of all Instagram posts (n=1370) from the 2024–2025 season. The findings demonstrate that successful digital interaction is built upon the club's local identity, the emotional drama of game events, and player brands. Fans evolve from passive followers to active value creators through a process of reciprocity, where the club rewards participation with visibility and a sense of appreciation. The central contribution of this study is the ‘Digital Fan Value Co-Creation’ framework, which shows value co-creation as a dynamic process. The framework also accounts for the challenges of this process, such as the gap between resources and aspirations and the risks of value co-destruction. It offers sports organizations a more realistic model for understanding and managing their digital fan communities by balancing the promotion of engagement with the management of its associated risks. Urheilun seuraaminen on kehittynyt digitaalisen murroksen myötä passiivisesta katsomisesta kohti emotionaalista sitoutumista ja yhteisöllisyyttä. Kiihtyvän murroksen myötä fanit eivät ole enää vain yleisöä vaan aktiivisia osallistujia, jotka luovat sisältöä, keskustelevat ja rakentavat kokemuksia yhdessä urheiluorganisaation kanssa digitaalisilla alustoilla. Fanien roolien muuttuminen on mahdollisuus ja samalla haaste urheiluorganisaatioissa, jotka pyrkivät säilyttämään merkityksellisyytensä ja taloudellisen elinvoimansa kilpailussa ihmisten vapaaajasta. Tämän tutkimuksen tavoitteena on selvittää, miten urheiluorganisaatio hyödyntää digitaalisia alustoja ja sosiaalista mediaa murroksen keskellä, kun tavoitteena on syventää fanisuhteita ja luoda arvoa yhdessä fanien kanssa. Sosiaalisen median käyttöä on tutkittu urheilumarkkinoinnissa usein vain organisaatioiden ja viestintästrategioiden näkökulmasta, jättäen käytännön prosessit vähemmälle huomiolle. Täydentääkseen nykyistä tutkimustarjontaa tämä tutkielma pureutuu syvälle arvon yhteisluomisen mekanismeihin digitaalisessa ympäristössä. Tutkimus tarkastelee ilmiötä urheilumarkkinoinnin ja suomalaisen ammattilaisurheiluorganisaation näkökulmasta, jossa intohimoisella fanikulttuurilla on merkittävä rooli. Tulokset pohjautuvat monimenetelmälliseen aineistoon, joka on kerätty triangulaatiomenetelmällä seuran markkinoinnista vastaavien haastatteluista, fanikyselystä (n=671) sekä koko sarjakauden (2024–2025) kattavasta Instagramjulkaisujen (n=1370) sisältöanalyysistä. Tutkimus osoittaa, että onnistunut digitaalinen vuorovaikutus rakentuu seuran paikallisen identiteetin, ottelutapahtumien emotionaalisen draaman ja pelaajabrändien ympärille. Fanit kehittyvät passiivisista seuraajista aktiivisiksi arvonluojiksi vastavuoroisuuden kautta, jossa seura palkitsee osallistumisen näkyvyydellä ja arvostuksen tunteella. Tutkimuksen keskeinen tulos on "Digital Fan Value Co-Creation" -viitekehys, joka kuvaa arvon yhteisluomista dynaamisena prosessina. Kehys huomioi myös prosessin haasteet, kuten resurssien ja tavoitteiden välisen kuilun sekä arvon yhteistuhoutumisen riskit. Viitekehys tarjoaa urheiluorganisaatioille realistisemman tavan ymmärtää ja johtaa digitaalisia faniyhteisöjään, tasapainotellen sitoutumisen edistämisen ja siihen liittyvien riskien hallinnan välillä.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development